Altitude exposure as a training & iron overload management strategy post leukemia. Issue 1 (January 2020) - Serpell, Benjamin G.; Freeman, Stephen; Ritchie, David; Choi, Philip; Périard, Julien D.; Sharma, Avish P.
Abstract: Objectives: To examine iron stores, hemoglobin mass, and performance before, during and after intermittent altitude exposure in a professional male rugby player experiencing iron overload following blood transfusions for treatment for acute myeloid leukemia. Design: Longitudinal, repeated measures, single case-study. Methods: The player was followed prior to (control), and during (study), an in-season block of altitude training. During the control period two venesections were performed for a total of 750 mL of blood removal. Internal and external training load, match statistics, blood volume, plasma volume, haemoglobin mass, serum ferritin and reticulocyte count were monitored throughout. Results: During the control period serum ferritin declined following the two venesections (∼51%) as did haemoglobin mass (∼2%), reticulocyte count remained stable. During the study period serum ferritin further declined (∼30%), however haemoglobin mass and reticulocyte count increased (∼4% and ∼14% respectively). Internal training load for the control and study period was similar, however external training load was lower in the study period. Match statistics were not favourable for the player during the control period, however they improved during the study period. Conclusions: This case supports the theory that individuals with elevated iron availability are well placed to achieve increases in haemoglobin mass. Furthermore, although therapeutic venesections may still be required to manage iron overload, the addition of altitude exposure may be a method to assist in reducing total body iron by means of mobilising available (excessive) iron to incorporate into haemoglobin. Altitude exposure did not hinder the players' performance. Further research is encouraged.